Resolving primary membranous glomerulopathy (MGN) reveals a dynamically metabolic pathway from sub-epithelium to glomerular basement membranes. (2nd January 2022) - Al-Othman, Yazan A.; Kroneman, Olaf; Kumar, Sandeep; Li, Wei; Kanaan, Hassan D.; Liu, Ming-Lin; Qu, Hong; Zhang, Ping L.
ABSTRACT: In idiopathic (primary) membranous glomerulopathy (MGN), there is a phenomenon of subepithelial deposits (stages 1 and 2) transitioned to intramembranous deposits, with lucent resolving features (stages 3 and 4). This phenomenon has not been described in other types of immune complex mediated glomerulonephritis with either subendothelial or mesangial deposits. The goal of this study was to evaluate what unique immunostaining pattern could occur in primary MGNs with intramembranous resolving features. PLA2R and IgG4 immunostains were performed in 50 primary MGNs, and 39 secondary MGNs after the clinical history was reviewed. Primary MGNs with resolving features were further evaluated in detail. A total of 84% (42/50) of primary MGN cases had diffuse positive immunostaining for IgG4 in the glomeruli, and most of them were also positive for PLA2R staining. Eight of the remaining primary MGN cases (8/50) with positive PLA2R but negative IgG4 staining in the glomeruli had diffuse resolving features as observed by electron microscopy. All secondary MGNs were stained negatively for both IgG4 and PLA2R except for one case with positive IgG4 staining but negative staining for PLA2R. Our data indicate that IgG4 staining on paraffin tissue is a very reliable screening tool to confirm the presence of primary MGN. Primary MGN with PLA2R+/IgG4- stains were seen in those with intramembranous resolving features. This finding is consistent with the known weak-binding capacity of IgG4 to the glomerular basement membranes. The transitional phenomenon from PLA2R+/IgG4+ subepithelial deposits to PLA2R+/IgG4- intramembranous resolving deposits in primary MGN implies that there may be a continuous metabolic activity from podocyte to glomerular basement membrane.